In response to complement anaphylatoxin peptides C3a and C5a, human vascular endothelial cells migrate and mediate the activation of B‐cells and polarization of T‐cells. Issue 6 (17th April 2020) - Shivshankar, Pooja; Li, Yi‐Dong; Mueller‐Ortiz, Stacey L.; Wetsel, Rick A.
Abstract: The vascular endothelium has been discovered in the past several years to be important in shaping the cellular immune response. During the immune response the vascular endothelium is constantly perturbed by biologically potent molecules, including the complement activation peptides, C3a and C5a. Despite the importance of C3a and C5a in inflammation and immunity, their role in modulating lymphocyte function via activation of vascular endothelial cells is unknown. Accordingly, we investigated the regulated expression of the C3a and C5a receptors (complement anaphylatoxin C3a receptor [C3aR] and complement anaphylatoxin C5a receptor 1 [C5aR1]) on human umbilical vascular endothelial cells (HUVECs) and examined how C3a or C5a activation of HUVECs affects the activation and polarization of lymphatic cells. Our findings demonstrated that C3a and C5a increase C3aR and C5aR1 expression by HUVECs as well as directing their cellular transmigration and spreading through transwell filters. Moreover, C3a‐ or C5a‐stimulated endothelial cells: (1) caused activation of B‐lymphoblasts with significant increase in Fas Ligand (CD95L) (FasL), CD69, and IL‐R1 expression, and (2) skewed T‐lymphoblast cells toward a Th1 subtype, (CD4 + /CCR5 + ) that correlated with significant increase of IFN‐γ. Collectively, these data indicate that C3a and C5a signaling is important in the activation and polarization of lymphocytes as they traffic through the vascular endothelium during the immune response.